Biosorption of copper ions using rhizobium phaseoli - Gur, Nazmi; Izgi, Nida; Topdemir, Aykut (Parlar Scientific Publications, 2020)
Potentially toxic concentrations of heavy metals in industrial wastewaters pose environmental problems. Biological molecules are an attractive alternative to oft-used physical and chemical processes for the removal of heavy metals from industrial effluents. One of those methods is biosorption, by which metal ions are transported into cell structure, and heavy metals are removed through several mechanisms between living/non-living microorganisms and metal ions. The aim of this study was to remove copper ions (Cu2 + ) from aqueous solutions. Two adsorptive isolates of Rhizobium phaseoli and Rhizobium phaseoli GAT 899, which is a strain adsorptive, were used. The effect of initial copper ion concentration, biosorption values, and pH and time parameters on removal process was determined. The highest removal rates of copper ions at pH 3, 250 mg/lt concentration, and 90t h min in Rhizobium phaseoli 23F isolate, Rhizobium phaseoli 38F isolate, and Rhizobium phaseoli GAT 899 strain were 53.35 mg/lt, 31.83 mg/lt, and 50.00 mg/lt, respectively. © by PSP.
Keywords: Biosorption; Copper ions; Heavy metal; Rhizobium phaseoli